1981
DOI: 10.1084/jem.154.6.1935
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone regulation of in vitro immune response. Estradiol enhances human B cell maturation via inhibition of suppressor T cells in pokeweed mitogen-stimulated cultures.

Abstract: Higher serum immunoglobulin (Ig) levels are usually observed in females more than in males of several mammalian species, including man. Females also show a quantitatively and qualitatively enhanced capacity to produce antibodies after immunization (1-7). Moreover, during their fertile period, women have remarkably higher incidences of autoimmune diseases (8, 9). On the other hand, reports exist (10) indicating that males have stronger cell-mediated responses than females. These sexdependent differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
2
4

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(88 citation statements)
references
References 28 publications
6
76
2
4
Order By: Relevance
“…1 nM in females, it is suggested that testosterone may suppress immunoglobulin production also in vivo under normal conditions. On the other hand, oestrogen has been shown to augment humoral immune responses [1,7,11,12,33], and we also found that this hormone increased spontaneous immunoglobulin production by human PBMC in vitro at physiological concentrations (paper submitted). Collectively, these data suggest that human humoral immune responses may be controlled by the balance of these sex hormone levels.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…1 nM in females, it is suggested that testosterone may suppress immunoglobulin production also in vivo under normal conditions. On the other hand, oestrogen has been shown to augment humoral immune responses [1,7,11,12,33], and we also found that this hormone increased spontaneous immunoglobulin production by human PBMC in vitro at physiological concentrations (paper submitted). Collectively, these data suggest that human humoral immune responses may be controlled by the balance of these sex hormone levels.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies also showed that testosterone treatment inhibited the progression of autoimmune diseases in mice [3][4][5][6][7][8] and chickens [9,10]. However, most of these studies used animal immune systems in vivo and there are few studies showing the in vitro effect of testosterone on human humoral immune responses [11,12]. Especially the cellular mechanisms for its effect have not been precisely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that oestrogen increases the plasma concentration of Ig in broiler chicks (Leitner et al, 1996), and causes an increase in Ig-containing cells in the oviduct, whereas progesterone does not show such effects (Zheng et al, 1997). Studies in mice showed that oestrogen enhanced B-cell maturation and increased antibody production (Wira and Sandoe, 1980;Paavonen et al, 1981 (1997) reported that the population of Ig-containing cells in laying hens and immature hens treated with DES was higher at the two ends of the oviduct. It may be concluded that specific immune functions (humoral immunity and cell-mediated reactions) in the chicken oviduct are stronger in the infundibulum and vagina in both sexually matured hens and immature hens treated with sex steroids.…”
Section: Introductionmentioning
confidence: 98%
“…The immunological activities of BPA may be mediated through estrogen receptor signaling, arylhydrocarbon receptor, and the peroxisome proliferator-activated receptor family of nuclear receptors [5] . Estrogen was shown to have immunomodulatory effects, particularly with respect to humoral immunity, and immunosuppressive effects [6,7] , particularly with respect to cellular immunity [28] . More recent studies demonstrate that estrogen increases the secretion of IFN-γ from splenic lymphocytes, which play a major role in regulating the function of all key immune cells [8,9] .…”
Section: Discussionmentioning
confidence: 99%
“…It acts as endocrine disrupter with estrogenic activities in the body. Estrogen has stimulatory effects on humoral immune responses [6,7] . More recent studies demonstrate that estrogen increases the secretion of interferon-γ (IFN-γ) from splenic lymphocytes, which play a major role in regulating the function of all key immune cells [8,9] .…”
Section: Introductionmentioning
confidence: 99%